Assessment of Changes in Corn Husk Fibres after Acid Treatment - Pragati Bajpai; Utpal Jana; Saminathan Ratnapandian (Tekstilec)
Sustainability is desirable in any activity, including farming. Adding value to agricultural wastes such as stover (waste from corn cultivation) would provide financial benefits to farmers while reducing the environmental load of disposal. The literature identifies stover as being a raw material for bio-ethanol and a reinforcement for composites. Fibre from corn husks is generally extracted using an alkali digestion method followed optionally by enzymatic degradation. In this study, acid treatment was investigated for its feasibility to improve the desirable characteristics of alkali extracted corn husk fibres. The results revealed that increasing the acid concentration decreased fibre properties such as average fibre length, linear density and elongation at break. However, breaking tenacity achieved a maximum value, on treatment with 7.5 g/l sulfuric acid, before decreasing. These properties indicate the treatment’s adequacy for use in textile products. Acid treatment did not significantly alter thermo-gravimetric analysis values, indicating that the fibre could withstand wet processing conditions.